Classification Method of Rock Structure and Rock Mass Quality of Surface Granite: Geological Disposal of High-Level Radioactive Waste in China - Wei Xiang; Hanlie Cheng; David Cadasse (Adsorption Science & Technology)
The engineering quality of rock mass is a key factor to evaluate the long-term stability and safety of high-level radioactive waste (HLW) geological disposal engineering and is also the important basis for disposal site selection. Traditional rock mass quality classification methods, such as RMR and Q, can meet underground engineering but still should be studied further for the site evaluation in the HLW disposal engineering. In this study, rock mass structure rating (RMSG) was proposed based on the quantitative control index of rock mass structure which was from the rock mass quality classification methods. Based on the statistical results of rock mass structure, the relationship between the number of RMSG and the modified RMR (FRMR) and Q (FQ) was established, China, as a case study. Results from this study show that RMSG is linearly related to FRMR and negatively exponential to FQ. The research results can solve the evaluation of rock mass quality for HLW geological disposal engineering, and the addition of more engineering examples over time will enable further verification.